The Effect Of Early Detection, Parenting, And Stimulation On Children's Independence - Musslifah, Anniez Rachmawati (Universitas Muhammadiyah Surakarta, 2025)
Children have every potential that is expected to develop according to their growth and psychological level. This paper aims to determine: first, is there a relationship between early detection, parenting, and stimulation on children's independence, and second, to determine the variables that have the most significant influence on children's independence. This study uses a quantitative approach. The results of the study indicate that the effect of early detection on children's independence is positive and significant, from the results of the t-test of 2.276 and a significance value of 0.047 and a regression coefficient of 0.185. The effect of parenting on children's independence is positive and significant, from the results of the t-test of 1.422 and a significance value of 0.162 and a regression coefficient of 0.060. The effect of stimulation on children's independence is positive and significant, from the t-test of 2.181 and a significance value of 0.034 and a regression coefficient of 0.288. The independent variable that has the most influence on children's independence is the early detection variable (X1), from the results of the t-test with a t-test value of 2.276, when compared to other independent variables.